As Reformas Educacionais e a Formação Humana na Rede Federal: avanços e retrocessos da integração curricular no Centro Federal de Educação Tecnológica de Minas Gerais – Campus Belo Horizonte (1997 a 2022) - Pedro, Helena Mara Dias (2023)
This thesis analyzes the educational reforms and the training of people in the federal network focusing on the advances and setbacks in the curricular integration of the Technical Course in Mechanics at the Federal Institute of Technological Education of Minas Gerais – CEFET-MG - Belo Horizonte Campus (1997 to 2022). Following the Marxist theory, progressive changes are considered as mediations and regressive changes as contradictions in the context of the historical and current movement of curriculum redesign, with integral training of people as a perspective. To achieve this goal, the curriculum policies of Lula’s and Dilma Rousseff’s governments (inclusion of Decree nº 5154/04 in the LDB) are considered progressive and the policies of Fernando Henrique Cardoso’s government, Presidents Temer and Bolsonaro (inclusion of Decree nº 2208/97 and later Law nº 13415/17), which separates secondary education from technical education, are considered regressive in order to show the contradictions and the differences brought by educational reforms to the social function of education from the perspective of integral human training. It is a study with a qualitative approach linked to an analitical perspective that takes into account quantitative. The paths of empirical research emerge from the document analysis that has allowed us to penetrate the reality of the Mechanics Technical Course at CEFET-MG and develop an understanding of the historical evolution of the course and the way in which the curricular structure positions itself in relation to educational reforms and the pedagogical models that circumscribe them. The documentary analysis has shown that the curricular configurations take on contours that result from educational reforms and their respective historical moment, characterizing what we call pedagogical models of professional education. It is possible to see that this path is followed by the institution, highlighting the following models: taylorist-fordist (1942 to 1997); technological-fragmentary (1997 to 2004); technological-integrated (2004 to 2013); and technological-fragmentary (2014 to 2022). In the period in which the technological-fragmentary model was in force, it was possible to identify the contradictions that constituted the greatest curricular distortions in the curriculum. On the other hand, the period of validity of the integrated technological model shows the mediations that favor the strengthening of integral human training at CEFET-MG. However, the changes proposed by REM again point to a contradiction that shows that the integral human training that guides professional education is under threat, which alerts us to a possible return to the fragmentary technological model. In the phase of the direct observation of the research object, we were able to identify the relationships and correlations of forces established in the institution in the current context of curricular reform in the different subjects. The reports lead us to confirm that there is a process of resistance to the implementation of the new secondary education, which is evident in the strategies created to undermine the fragmented curriculum prescribed in the current guidelines. Such strategies range from completely denying implementation to even the possibility of constructing a curricular review incorporating adjustments to meet market demands. The curriculum is a territory crossed by institutional disputes. The tensions in its conception explain the changes in the pedagogical models of this process. The discourse of flexibility, which is translated into crumbling content in the reform, restores the fragmentary technological model without representing a simple return to the past, but the understanding that it now takes on even more accentuated contours due to the complexity of the contemporary scenario of regression, first as a tragedy and now as farce (Marx, 1952, Eighteenth Brumaire of Louis Bonaparte).